The influence of increased protein intake and L-carnitine supply on the outcomes of term newborns in intensive therapy - I. O. Anikin; L. S. Stryzhak (Zaporozhye State Medical University, 2023)
We studied the possibilities of increased protein and L-carnitine supplementation in full-term newborns with perinatal diseases to improve the results of intensive care. Aim: to assess the impact of short-term increased protein consumption and L-carnitine supplementation by full-term newborns on the main indicators of treatment effectiveness in the intensive care unit. Materials and methods. To check the impact of the proposed method of feeding newborns, the life indicators of 59 full-term children, who were randomly divided into two groups, were studied. The first group (n = 30) received standard nutrition with mother's milk or formula, the second group (n = 29) received a food product fortified with a protein supplement and a subsidy of L-carnitine during hospital stay. Results. Infants of both groups had statistically equivalent anthropometric characteristics at the beginning of the study. The proportions of infants of both sexes were within the 50 % percentile. Starting from the third week, caloric intake for the standard diet group (SG) and the enrichment group (FG), respectively, was 111.83 ± 7.19 kcal/kg/day, against 113.44 ± 5.61 kcal/kg/day, p = 0.0667. Per 1 g of protein, children in the FG group had amount of non-protein calories as 28.68 (27.50; 29.80) kcal/kg/day, compared to the indicator in the SG group of 42.37 (41.60; 38.00) kcal/kg/day, with U = 28.0000; p = 0.0001. Carnitine supplementation in the FG group led to an increase in the level of free carnitine in the last blood plasma samples, before the children were discharged home. In general, the proposed nutrition strategy was accompanied by better indicators of the physical development of children, and a statistically probable faster recovery of body weight in the fortification group. Thus, the generalized indicator of body weight of children of the SG group was 3966.90 ± 439.08 g, compared to the FG group of 3554.62 ± 452.28 g, with p = 0.0033. In general, children who consumed more protein were transferred from the intensive care unit earlier - 12.00 (11.00; 16.00) days, against 10.00 (8.00; 12.00) days, with U = 235,00; p = 0.0024; previously discharged from the hospital - 26.50 (22.00; 31.00) days, against 21.00 (19.00; 27.00) days, with U = 267.00, p = 0.0109. This strategy proved to be safe, as confirmed by normal levels of phenylalanine and urea at all stages of the examination of children. Conclusions. Short-term increased protein consumption against the background of carnitine supplementation improves the results of physical development of newborns and indicators of hospitalization and intensive care unit stay. Larger studies and catamnestic observation of children are needed.